Pengaruh Penyiraman dan Dosis Pemupukan terhadap Pertumbuhan Kangkung (Ipomoea reptans) pada Komposisi Media Tanam Tanah+Pasir - FAUZI, AHMAD RIFQI (Agrotrop : Journal on Agriculture Science; Vol 4 No 2 (2014), 2015)
Effect of Water Requirment and Fertilization on Growth of Kangkong (Ipomoea reptans) in media composition soil+sand. Kangkong plant is a tropical vegetable widely cultivated in Indonesia. Village has a wide adaptability to climate and soil in the tropics. This experiment aimed to see the effect of watering and fertilization on the growth of kangkong plants. Experiments was carried out in the garden experiment Cikabayan, IPB on March-April 2011. This experiment was arranged with randomized complete design which consisted of two factors are 3 levels of watering (watering every 1 day (A1), every 2 days (A2), and every 3 days (A3)) and fertilization with 5 doses (100% dose recommendation (P1), 75% (P2 ), 50% (P3), 25% (P4), and 0 (P5)). Planting medium was a mixture of soil : sand (1:1). The results of this study indicate that the frequency of watering significant effect on plant height and weight of wet kangkong plants. Watering once every 2 days to produce the highest plant height (41.41 cm). While fertilization had no effect on all observed variables. Conclusion of the experiment is watering is one of important factor for plant production which significant effect on plant growth.
Keywords: Kangkong; Water requirement; Fertilization; plant growth